Non-monotonic bounded reasoners (The Reasoner, 2025)
We put forward a proposal for logics handling both non-monotonic reasoning and boundedly rational agents. We propose a hierarchy of depth-bounded non-monotonic logics. As the parameter k, which controls the level of reasoning depth, increases, non-monotonicity decreases while inferential power, in a classical sense, increases. Ultimately, these logics aim to provide non-monotonic approximations of classical logic. We present arguments and evidence supporting the adoption of this framework.
Keywords: logic programming; depth-bounded boolean logics; non-monotonic reasoning; bounded rationality